2020
DOI: 10.1088/2058-6272/abae4a
|View full text |Cite
|
Sign up to set email alerts
|

Electron population properties with different energies in a helicon plasma source

Abstract: The characteristics of electrons play a dominant role in determining the ionization and acceleration processes of plasmas. Compared with electrostatic diagnostics, the optical method is independent of the radio frequency (RF) noise, magnetic field, and electric field. In this paper, an optical emission spectroscope was used to determine the plasma emission spectra, electron excitation energy population distributions (EEEPDs), growth rates of low-energy and high-energy electrons, and their intensity jumps with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This shift in light corresponds to a jump in density, as shown in figure 6(c). Existing literature shows that the light radiated from plasma jumps from pink light to blue light, which is a manifestation of neutral depletion and high ionization rate [41], and the ionization rate can even reach nearly 80% [6]. After the appearance of the blue core mode, as the power decreases, it can be found that the blue core can exist at a lower power than the previously mentioned threshold power until it falls below another threshold power, that is, downward threshold power, where the blue core mode disappears.…”
Section: Discharge Characteristics and Parameters Scanningmentioning
confidence: 99%
“…This shift in light corresponds to a jump in density, as shown in figure 6(c). Existing literature shows that the light radiated from plasma jumps from pink light to blue light, which is a manifestation of neutral depletion and high ionization rate [41], and the ionization rate can even reach nearly 80% [6]. After the appearance of the blue core mode, as the power decreases, it can be found that the blue core can exist at a lower power than the previously mentioned threshold power until it falls below another threshold power, that is, downward threshold power, where the blue core mode disappears.…”
Section: Discharge Characteristics and Parameters Scanningmentioning
confidence: 99%